Manufacturing Outsourcing to Achieve Organizational Performance through Manufacturing Integrity Capabilities - Shanmugan, Muralitharan; Shabir Shaharudin, Muhammad; Ganesan, Yuvaraj; Fernando, Yudi (KnE Social Sciences, 2019)
Manufacturing companies outsource their manufacturing process to achieve organizational performance. Companies can focus on improving their core business processes while leaving manufacturing process to companies that are more efficient and cost-effective. However, this leaves manufacturing companies with a dilemma as those outsourcing companies are also producing for competitors and companies’ brand is liable to the integrity of outsourcing companies. By having integrity capabilities, it is argued that companies can achieve organizational performance. This paper investigates the relationship between manufacturing outsourcing and organizational performance with the mediating effect of manufacturing integrity capabilities. This paper contributes to the body of literature by investigating the impact of manufacturing integrity capabilities with resource-based view and transaction cost economics theories. Furthermore, this paper also is practically useful for companies to understand integrity capabilities that are useful to increase organizational performance in the era of the dynamic business environment.